2010
DOI: 10.4309/jgi.2010.24.5
|View full text |Cite
|
Sign up to set email alerts
|

Online crime and internet gambling

Abstract: The spread of Internet gambling has raised several issues concerning motivations to gamble, consumer behaviour online, problem gambling, security of Web sites, and fairness and integrity of the games. Rather surprisingly, however, there has been little in the way of research regarding online crime and Internet gambling even though it is an urgent priority. This article addresses this absence by investigating the types, techniques, and organizational dynamics of online crime at the portals of Internet gambling … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(12 citation statements)
references
References 21 publications
(15 reference statements)
0
12
0
Order By: Relevance
“…Since the first Internet casino gambling site was launched in 1995, increased access to the Internet and Internet gambling has changed the gambling scene globally and raised several issues concerning gambling and problem gambling (McMullan & Rege, 2010;Potenza et al, 2011;Watson, Liddel Jr., Moore, & Eshee Jr, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Since the first Internet casino gambling site was launched in 1995, increased access to the Internet and Internet gambling has changed the gambling scene globally and raised several issues concerning gambling and problem gambling (McMullan & Rege, 2010;Potenza et al, 2011;Watson, Liddel Jr., Moore, & Eshee Jr, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Concerns regarding fair play practices are reasonable as there are numerous examples of online gambling sites not paying winnings, cheating players with unfair games, or stealing deposits and personal details (Gainsbury, 2012;McMullan & Rege, 2010). The Australian Productivity Commission gambling inquiry (2010) concluded that increased legalization and regulation of online gambling would be more effective than prohibition to protect residents from harm as this would result in increased consumer choice and higher standards for sites that would have to compete for customers.…”
Section: Consumer Protectionmentioning
confidence: 99%
“…Moreover, criminological studies (McMullan and Rege 2007, 2010McMullan, 2012;Banks, 2013Banks, , 2014 have highlighted the multiplicity of ways in which gambling and crime intersect in online environments. Online gambling can operate as source of criminal activity, as a vehicle for crime or support for other criminal enterprise, with incidents of match fixing, distributed denial of service (DDoS) and cyberextortion, illegal and underage gambling, fraud, theft and money laundering having been identified by researchers.…”
Section: Understanding Gambling-related Crimementioning
confidence: 99%